Acquisition and monitoring of multichannel ECG - S. Khan, Md. Mashrur; Md. Ashraf-Ul-Karim; Awan, Shah Md. Sibbir (BRAC University, 2011)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2010.